POLA KOMUNIKASI KELOMPOK KOMUNITAS SPARTAN KOMANDO (SPARKO) JAKARTA DALAM MEMPERTAHANKAN EKSISTENSINYA - Sofiawati, Selvi; Pratiwi, Wulan Dwi; Pranawukir, Iswahyu (DIALEKTIKA KOMUNIKA: Jurnal Kajian Komunikasi dan Pembangunan Daerah, 2023)
The Sparko Community is a military-style sports community formed by Lt. Col. Eka Wira in 2015. This community already has many members spread across several cities in Indonesia, one of which is the Sparko GBK Community in Jakarta. The aim of this research is to find out how group communication patterns maintain their existence through the concept of network type theory of communication patterns. The research method is descriptive qualitative. Data collection methods include observation, interviews, literature study and documentation. The informants in this research were represented by 4 people, namely 1 person was a coach as key informant and 3 people were members and community administrators as informants. The research results show that the communication pattern that occurs in the Sparko community is an all-channel communication pattern or a Bintang communication pattern where the chairman and members have the same power in influencing other members and all members can send and receive messages actively and communicatively, and everyone can communicate and participate optimally in the group. Keywords : Communications Pattern, Existence, Sparko Community